Relationship between Gen Z’s Personality and Motivations with TikTok Usage During Pandemic - Krisadhi, Risa; Kurniyawan, Dede; Aryawan, Dewi Nandini; Johan, Hanni Shabrina; Ishomi, Muhammad Ikbar (UPT Publikasi Ilmiah UNISBA, 2023)
The COVID-19 pandemic has significantly reshaped how people communicate due to restrictions on direct interaction, impacting both mental and physical well-being. Social media, particularly TikTok, gained widespread attention during the pandemic, notably among Gen Z, offering online expression and entertainment to compensate for limited in-person interaction. However, the interplay between Gen Z's personality traits, motivations, and TikTok usage remains relatively unexplored. In order to fill the gap, this research investigates how Gen Z's personality traits influence TikTok media usage, considering the mediating role of motivations during the pandemic. Employing the Uses and Gratifications framework and the Big Five Personality factors, the research collected data from 400 Gen Z participants in the Jabodetabek and then analyzed by Path Analysis. The findings show that personality traits do influence TikTok usage, mediated by motivations for information seeking and sharing, social interaction, escapism and relaxation, as well as norm and trend following. In this research, the classification of the Big Five Personalities was different because the research only found four types of personality in Gen Z: extraversion, conscientiousness and neuroticism, agreeableness, and openness. Gen Z's motivation for using TikTok during the COVID-19 pandemic differs for each personality.